Kajian Eye-Tracking Pengaruh Gender Terhadap Proses Kognitif dalam Pembelajaran Multimedia - AG Pradnya Sidhawara; Sunu Wibirama; Dwi Joko Suroso (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2023)
Multimedia learning is defined as the process of forming a knowledge mental model from words and pictures. It is important to measure cognitive process during multimedia learning. Differences in learners’ capabilities can be investigated through cognitive processes to improve the learning process. However, conventional methods such as interviews or behavioural assessment do not provide an objective measurement of cognitive processes during multimedia learning. Some advance methods to measure cognitive processes takes into account learner’s eye movement during learning process. In such a case, eye-tracking can be used as an alternative method to measure cognitive processes because eye movement has become a major part of human cognitive function. Another issue is related to the learners with different gender, which might have different styles of interaction with the source of information. Unfortunately, the effect of gender disparities in multimedia learning has not been widely studied. To address this research gap, this study examines the effect of gender differences based on eye-tracking metrics during multimedia learning. Based on the experimental results, `time until first fixation` on the text-type area of interest (AOI), `number of fixations` on the image type AOI, and `transition` from text-type AOI to image-type as well as `transition` between Image AOIs provided notable distinctions for each gender group (p < 0.05). It was found that male learners preferred to access information from images. In contrast, female learners tended to do a thorough inspection on textual and pictorial information during multimedia learning. This study can be used as an alternative method for collecting cognitive process indicators in multimedia learning.